ANALISIS KEPUASAN DAN LOYALITAS KONSUMEN KOPI BUBUK SINAR BARU CAP BOLA DUNIA (SB-CBD) DI KOTA BANDAR LAMPUNG - Adiguna Gadung; Wan Abbas Zakaria; Ktut Murniati (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
This study aims to determine the highest satisfaction level of SB-CBDproduct attributes, analyze the level of customer satisfaction coffee powder SB-CBD, analyze the level of loyalty coffee powder SB-CBD, and know the relationship between customer satisfaction and loyalty of coffee powder SB-CBD. This research was conducted in the city of Bandar Lampung purposively.The number of consumer respondents as many as 60 people, using accidental sampling. The data was analyzed by descriptive analysis, analysis of Consumer Satisfaction Index (CSI), analysis of Important Performance Analysis (IPA), pyramid loyalty and Rangk Spearman correlation analysis. The results showed that there were five atributs which had the highest satisfaction namely halal label, taste, price, aroma, and expiration dates.  The level of customer satisfactionofcoffee powder SB-CBD belonged to satisfied criteria and promotion attributes needed to be improved for better company’s performance.  The level of consumer loyalty of coffee powder SB-CBD belonged to the category of loyal because the majority of consumers as described in pyramid loyalty were at the level of liking the brand.  There is a positive relationship between the level of satisfaction and loyalty coffeepowder SB-CBD. Key words: coffee powder SB-CBD product, CSI, IPA, satisfaction, loyalty